Penanganan kasus bidang politik dalam pembelajaran Pendidikan Kewarganegaraan - Nasiwan Nasiwan (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
The teaching of Civic Education in Indonesia, especially on politics, from the perspire if its content is the most dynamic element in comparison to moral rapid change due to reformation undergone in Indonesia since May, 20 1998 or often is called as transitional democracy. In the period of transitional democracy since that time up to the end of 2006, many aspects of political affair has been changing radically both in super structures and in infrastructures politic. As a result, the teaching of civic education, especially on politic as its materials, needs of handling of political cases accurately. The goal is to avoid misconception; its approaches, as well as its methods of teaching.